Cross-Border Cooperation: Challenges and Perspectives for the Horizontal Dimension of European Integration - J. Beck (Управленческое консультирование)
Cross-Border Cooperation: Challenges and Perspectives for the Horizontal Dimension of European Integration.Continuation. See the beginning: Administrative consulting. 2018. N 1. P. 56–62.This article is based on a lecture given by the author at the North-West Institute of Management (NWIM), Branch of RANEPA, Faculty of International Relations on 16 May 2017 during a study visit of a delegation from the University of Applied Sciences, Kehl.